2021
DOI: 10.1192/bjo.2021.37
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mental health awareness in emergency services (the ENHANcE I project): cross-sectional survey on mental health stigma among emergency services staff

Abstract: Background The number of mental health-related 999 calls to emergency services has increased in recent years. However, emergency services staff have an unfavourable reputation when it comes to supporting people experiencing mental health problems. Aims To assess the levels of explicit and implicit mental health stigma among accident and emergency, ambulance and police staff, and draw comparisons with the general population. Additional analyses sought to identify which variables predict m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…as registered healthcare professionals, paramedics face barriers to disclosure and help-seeking for mental health problems and suicidality, including concerns around confidentiality and mandatory reporting. Of note, previous studies have found ambulance personnel report low rates of help-seeking and high levels of stigma (Haugen, McCrillis, Smid, & Nijdam, 2017;Hazell et al, 2021;Rikkers & Lawrence, 2021). Further research into occupation-specific risk factors for suicide among ESW is needed and will be essential to inform future suicide prevention efforts for these groups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…as registered healthcare professionals, paramedics face barriers to disclosure and help-seeking for mental health problems and suicidality, including concerns around confidentiality and mandatory reporting. Of note, previous studies have found ambulance personnel report low rates of help-seeking and high levels of stigma (Haugen, McCrillis, Smid, & Nijdam, 2017;Hazell et al, 2021;Rikkers & Lawrence, 2021). Further research into occupation-specific risk factors for suicide among ESW is needed and will be essential to inform future suicide prevention efforts for these groups.…”
Section: Discussionmentioning
confidence: 95%
“…Both workplace trauma exposure (Harvey et al, 2016; Milligan-Saville et al, 2018) and reluctance to seek help (Carlan & Nored, 2008) have been highlighted as significant contributors to these elevated rates. Whilst there has been improved awareness and provision of mental health support to ESW in recent years (Lawrence et al, 2018; Varker et al, 2018), stigmatising attitudes and low rates of help-seeking still persist among the emergency services (Hazell, Koc, O'Brien, Fielding-Smith, & Hayward, 2021; Rikkers & Lawrence, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 1 The effects of mental health stigma are pervasive: stigma reduces help-seeking, 2 , 3 has adverse economic implications via increased unemployment and healthcare costs, 4 and worsens both the mental 5 and physical health 6 of the stigmatised individual. Although mental health stigma may have improved over time, 7 , 8 current levels are still problematic. 9 …”
mentioning
confidence: 99%